The Intersection of IoT, Marketing, and Cybersecurity: Advantages and Threats for Business Strategy - Yamin, Ahmad Bin; Talla, Rajasekhar Reddy; Kothapalli, Srinikhita (Asian Business Review, 2025)
This paper examines how IoT, marketing, and cybersecurity affect current corporate strategy, including its benefits and drawbacks. The research examines how data-driven insights from IoT improve marketing tactics and the cybersecurity risks of linked devices. The research synthesizes secondary data to explore the dynamic interaction between IoT, marketing, and cybersecurity. The key results show that IoT helps organizations create targeted marketing campaigns using real-time data, but it also increases the attack surface, posing cybersecurity threats. Many IoT devices lack security and data privacy, which threatens corporate operations. The report also stresses integrating strong security measures into design, using adaptive security frameworks, and collaborating between marketing and IT departments. Policy implications include enterprises implementing more apparent cybersecurity principles and educating employees, while legislators should regulate data privacy, secure gadget manufacture, and cross-sector cooperation. This report emphasizes balancing innovation and security to maximize IoT-driven marketing tactics while minimizing cybersecurity concerns.
Keywords: Internet of Things (IoT); Marketing Strategies; Cybersecurity; Data Privacy; Business Strategy; IoT Security; Data-Driven Marketing; Consumer Trust; IoT Risks